The potential use of Pediococcus spp. probiotic in aquaculture: A review - Mohammed, Elshafia Ali Hamid; Ahmed, Abdelhakam Esmaeil Mohamed; Teye-Gaga, Christopher; Pál , Károly (Acta Agraria Debreceniensis, 2025)
Aquaculture production has significantly increased over the previous few decades. However, antibiotics have been implemented regularly and extensively to overcome outbreaks of pathogens in aquaculture to cover the human needs for animal protein, leading to the appearance of resistant strains that may cause serious damages in the environment and also human health. In the last few years, the implementation of probiotics as an alternative technique to antibiotics use in fish production has achieved promising results in aquaculture due to their beneficial impact on fish health and growth performance. Among different types of probiotics, the Pediococcus spp. bacteria stand out as a promising probiotic for their beneficial impact to aquaculture. Thus, the current study has been conducted to give an overview about the interactions between Pediococcus spp. and aquaculture. In addition, this review highlights the role of Pediococcus spp in promoting growth performance, improving feed conversion ratios and the intestinal architecture, enhancing the immune response and inhibiting fish pathogens, thereby preventing or at least reducing the use of antibiotics. Practical use of Pediococcus spp. probiotic in aquaculture as feed additives through selected case studies is also considered.